E-Government Usage: Taxpayers' Determining Factors in Using The E-Filing Application in Dumai City - Dedy Afrizal; Riski Ikbal Saputra; Deby Ilyanzah (Pascasarjana STIE Amkop Makassar, 2023)
This study examines methods for discerning the intentions of E-Government users regarding the use of government-owned applications for tax activity reports via e-filing applications. A quantitative methodology was used in this research. This study uses an additional construct known as attitude in addition to the primary variables derived from the UTAUT model, namely PE, EE, SI, FC, and ITU. The population consists of Dumai citizens who used the e-filing application. The study's sample comprised one hundred participants who completed an online survey via Google Form. The sampling method utilized was proportional random sampling. This study utilizing research instruments that have been adapted from previous research. The study utilized SEM Analysis with Smart PLS 3.0 software for data analysis. The obtained research results indicate that the relationship between EE and ITU, which is mediated by ATT, is only Partial Mediation. In contrast, the ATT-mediated relationship between PE and ITU is full mediation. Keywords: E-Government, UTAUT Model, E-Filing